Ultraestructura de bambúes del género Dendrocalamus (Poaceae: Bambusoideae) cultivados en Costa Rica I: Dendrocalamus latiflorus - Montiel, Mayra; Sánchez, Ethel (Revista de Biología Tropical, 2006)
The bamboo Dendrocalamus latiflorus is easily affected by sudden changes in temperature and humidity, which cause it to bloom. We used a scanning electron microscope to describe the ultrastructure of young culm (2 years old), culm bracts, buds, abaxial surface of the leaf lamina and flowers. The most noticeable ultrastructural features were the presence of two types of operculated cells in the sterile flower glums, the abundant cuticular wax, the presence of reticulated punctuations in the xylem and pollen grains with interlocking disks or cups. The operculated cells and the interlocking disks are taxonomically important features. Rev. Biol. Trop. 54(Suppl. 2): 43-50. Epub 2006 Dec. 01.